Microstructures, mineral chemistry, noble gases and nitrogen in the recent fall, Bhuka iron (IAB) meteorite. (15th October 2016) - Murty, S.V.S.; Ranjith, P.M.; Ray, Dwijesh; Ghosh, S.; Chattopadhyay, Basab; Shrivastava, K.L.
Abstract: We report some chemical, petrological and isotopic studies of the Bhuka iron meteorite that fell in Rajasthan, India in 2005. Numerous silicate and graphite inclusions are visible on the surface of the hand specimen. In the polished and etched surface studied, irregular patches of graphite are found as the most dominant inclusion and commonly associated with pure corundum (95 wt% Al2 O3 ), spinel, feldspar and Si-rich phases. Apart from typical lamellar intergrowth with kamacite (i.e. the Widmänstatten pattern), taenites are also commonly found to occur as a rim of the graphite inclusions. P-rich (up to 10 wt%) taenites are also found locally within the recrystallised kamacite matrix. Based on mineralogy, texture and bulk composition, Bhuka resembles the low-Ni IAB subgroup (ungrouped). Noble gas isotope studies suggest He, Ne and Ar are mostly of cosmogenic origin, while Kr and Xe are a mixture of cosmogenic, radiogenic and trapped components. A pre-atmospheric radius of 10±1 cm and a cosmic ray exposure age of 346±52 Ma are derived based on depth dependant ( 3 He/ 4 He)c and 38 Arc respectively, as per the production systematics of cosmogenic noble gas isotopes (Ammon et al., 2009). Cosmogenic 83 Kr and 126 Xe yield production rates of 12 and 0.335 ( in 10 −15 ccSTP/g Ma) for 83 Kr and 126 Xe respectively. Presence of trapped Kr and Xe, with ( 84 Kr/ 132 Xe)t =2 and radiogenic 129 Xe=120×10 −12 ccSTP/g are due to presence of graphite/silicate inclusions in the analysed sample. Over 150% excess 131 Xec than expected from spallation suggests contribution from (n, ɤ) reactions from Ba from inclusions and suggests irradiation of pre-atmospheric object in a larger body, indicative of complex irradiation. Trapped N of 24 ppm, with δ 15 N=−10.7±0.8‰ observed in Bhuka, is heavier than the range observed hither to in IAB irons. Highlights: Bhuka iron meteorite has been classified as IAB ungrouped. Pre-atmospheric radius determined as 10 cm, and cosmic ray exposure age as 346±52 Ma. Presence of nucleogenic 131 Xe suggest complex irradiation of Bhuka Isotopic composition of N is heavier than hitherto found in IAB irons.